SPF Activity Sunscreen Spray Gel Ethanol Extract of Cinnamon Bark (Cinnamomum burmanii Ness. BI, Syn) - Sari, Wulan K.; Kristantri, Rika S.; Pebriani, Tris H. (Jurnal Akademika Kimia, 2023)
This cinnamon bark contains cinnamaldehyde, which is a secondary metabolite compound derived from aldehydes, including the polyphenolic group, which activity as a sunscreen and antioxidant by absorbing UV rays, so it can protect the skin from direct sun exposure (sunscreen). The study aimed to determine whether there was an effect of the concentration of the ethanol extract of cinnamon bark (Cinnamomum burmanii Ness. BI, Syn) on the physical characteristics and SPF value of spray gel preparations and to determine the concentration of the ethanol extract of cinnamon bark that produced spray gel with physical characteristics and SPF value. best. The study was conducted by extracting cinnamon bark by the maceration method using 96 % ethanol for 3 days. The extract obtained was then subjected to phytochemical screening TLC and then applied to a spray gel preparation with concentrations of FI (10 %), FII (15 %), and FIII (20 %), followed by testing the activity of sunscreen using the UV-Vis spectrophotometry method. The results of phytochemical screening and TLC on the ethanol extract of cinnamon bark showed positive results for containing flavonoids, alkaloids, tannins, steroids, and antioxidants. The statistical test results showed that there was a difference with a sig value of 0.05. It was concluded that the ethanol extract of cinnamon bark affected pH, viscosity, spreadability, stickiness, drying time, and SPF value. The formula that gave the best physical characteristics and SPF value was found in the concentration of sunscreen spray gel: the ethanol extract of cinnamon bark with a concentration of FIII (20 %).